Investigating Chef-Leader Behaviour Impacts on Subordinate Work Team Identification: A Pitch - Matthew L. Brenner (Journal of Accounting and Management Information Systems (JAMIS), 2016)
This pitch letter outlines my personal experience applying Faff's (2015a) two-page pitching template to my PhD research plan. It discusses how the process of completing the pitching template has enabled me to better organise and articulate my research plan. This letter provides support for the use of the pitching template to evaluate and assess research which is beyond the initial stages of development. This letter describes how the pitching process systematically enables a researcher to not only conceptualize a research plan, but also enables a researcher to critically evaluate and assess an already established research plan for greater clarity.
Keywords: M10; M11; M54; 650; pitching research; leadership; team identification; chefs